(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
The independent work of students is the main and important organizer of the process of obtaining Science in higher education. In many developed countries, more than half of the total educational time is allocated to this. This is a huge reserve for achieving educational goals in science. Unfortunately, in practice it is not fully used, sometimes it goes unnoticed by the teacher. In order to eliminate these shortcomings, a huge number of ways of organizing independent work have been developed.